The relationship between serum vitamin D level with inflammatory markers and Total Antioxidant Capacity in Oral lichen planus - Hu, Yuhan (Cellular and Molecular Biology, 2022)
Inflammatory markers play an important role in the pathophysiology of patients with oral problems such as oral lichen planus. This study aimed to investigate the relationship between vitamin D levels and inflammatory markers and total antioxidants in people with oral lichen planus. In this case-control study, 131 patients with oral lichen planus (67 in the lichen planus group and 54 in the control group) were examined. 8 cc of blood was taken from all participants to assess blood factors, inflammatory markers and antioxidant levels. Data were analyzed using SPSS statistical software. The mean age of subjects was 42 years. Vitamin D3 levels in the lichen planus group were lower than in the control group, but this decrease was not statistically significant (P> 0.05). According to statistical findings in the lichen planus group, there was a significant relationship between vitamin D3 levels, inflammatory markers and cellular stress factors (P≤0.05). It is concluded that vitamin D3 in people with oral lichen planus can play an important role in the pathogenesis of oral disease and increase inflammation. Because patients with oral lichen planus are affected by various inflammatory factors, paying attention to vitamin D levels in these patients can be effective in reducing inflammation caused by lichen planus.